MODEL KOMUNIKASI KESEHATAN ISLAMI DALAM TRADISI PESANTREN - Uud Wahyudin (Jurnal Ilmu Komunikasi Acta Diurna, 2017)
Culture will affect the way, style, perception of the object in communicating. Conversely,communication builds a culture owned by groups, ethnic, race, ethnicity, and nation. In thepesantren tradition, developing a life-long teacher-student relationship system for both kyai andsantri. Tradition of the pesantren with the uniqueness of the cultural framework, has a differentcommunication behavior with the behavior in public education. In accordance with the learningtechniques known in the tradition of pesantren, such as sorogan, bandongan, and so on, then theprocess of delivering health communication messages occur in the learning process. Each santriinterpreted an object based on a process of reflection on everyday experience that is internalizedinto value. These values are also underlying students perform an election or decision-making inhis life. This study aims to find a model of health communication developed in the tradition ofboarding schools. In the pesantren tradition, health communication that develops is interpersonalhealth communication, group health communication, and health communication organization. Inthis research found three mean of health communication proposed by santri based on consciousexperience that is health communication which is process of delivering health and hygieneinformation which usually done by kyai to santri at sorogan, group health communication atbandongan, and health communication organization at when discussing activities or healthprograms undertaken.